Self-regulation through goal setting - Alexander K. Koch; Julia Nafziger (Institute for the Study of Labor (IZA), 2008)
Goals are an important source of motivation. But little is known about why and how people set them. We address these questions in a model based on two stylized facts from psychology and behavioral economics: i) Goals serve as reference points for performance. ii) Present-biased preferences create self-control problems. We show how goals permit self-regulation, but also that they are painful self-disciplining devices. Greater self-control problems therefore lead to stronger self-regulation through goals only up to a certain point. For severely present-biased preferences, the required goal for self-regulation is too painful and the individual rather gives up.
urn:nbn:de:101:1-20081219153
Keywords: A12; C70; D91; 330; Goals; self-control; motivation; time inconsistency; psychology; Leistungsmotivation; Persönlichkeitspsychologie; Verhaltensökonomik; Präferenztheorie; Zeitkonsistenz; Theorie